Case Report: Ovulation Induction in Greater One-Horned Rhinoceros (Rhinoceros unicornis) - Hermes, Robert; Balfanz, Folko; Haderthauer, Simone; Dungl, Eveline; Hildebrandt, Thomas B.; Schwarzenberger, Franz (Frontiers in Veterinary Science, 2021)
Despite a profound knowledge on reproduction biology in greater one-horned (GOH) rhinoceros, many individuals cope with sub or infertility or an-ovulatory estrous. At the same time, early and regular captive breeding is of high importance in female GOH rhinoceros due to their high prevalence to develop genital tract tumors with consequent cessation of reproduction. Thus, mature, an-ovulatory GOH rhinoceros represent a challenge for captive breeding programs and warrant for means of reliable ovulation induction. Here, we used hCG and GnRH analog histrelin to induce ovulation in an-ovulatory GOH rhinoceros. Upon ultrasound diagnosis of a preovulatory follicle hCG or GnRH were injected to induce ovulation (n = 11). As a result, 75% of the hCG (n = 6/8) and 33% of GnRH (n = 1/3) inductions resulted in ovulation. Ovulation occurred when fecal estrogen concentration increased before and pregnane concentration after induction. Thirty-six percent of all treatments (n = 4/11) failed to induce ovulation. When ovulation induction by hCG/GnRH injection failed, estrogen and pregnane concentrations were significantly lower compared to ovulatory estrous (P < 0.001). Our results suggest that hCG and GnRH analog facilitate an easily applicable treatment to induce ovulation in females with behavioral but at times an-ovulatory estrous. Frequent use of hCG as an ovulation inducer might help to achieve pregnancies in genetically important but an-ovulatory GOH rhinoceroses.